No increased drought-related mortality after thinning: a meta-analysis - Willig, Julius; Schwarz, Julia; Comeau, Philip; Hartmann, Henrik; Kohnle, Ulrich; Espelta, Josep Maria; Mäkinen, Harri; Ogaya, Roma; Peltoniemi, Mikko; Penuelas, Josep; Roth, Brian; Ruiz-Peinado, Ricardo; et al. (BioMed Central, 2025)
Context Forest scientists are challenged to identify and propose evidence-based silvicultural options to mitigate the impacts of drought events induced by climate change. For example, it has been suggested that thinning increases soil water availability for individual trees by reducing stand density and stand-level transpiration. Many studies have assessed the impact of thinning on stem growth and transpiration of individual trees during and after drought events. Often, growth increases were observed, but not consistently, and their impact on tree survival following drought has rarely been addressed. Aims We aimed to assess the effect of thinning on tree mortality, the ultimate indicator of tree resistance to soil water deficit induced by drought, with a focus on dominant trees. Methods We conducted a risk ratio meta-analysis on tree mortality before and after an extreme drought event with 32 thinning experiments from nine studies in Europe and North America. Results We showed that thinning reduced the overall mortality risk of trees. However, the lower mortality rate in thinned stands relative to unthinned stands in pre-drought periods was not further reduced during and after extreme drought events (p > 0.05). This may be due to the large heterogeneity and inconsistent reporting of mortality across the studies included in our analysis. Thinning did not exacerbate mortality among dominant trees. Conclusion Since thinning did not increase mortality, its application can still be recommended for many other management objectives such as maintaining tree species richness or lower disturbance risks from windthrow. We propose better documentation of thinning trials to improve the data base for systematic reviews.
Keywords: drought resistance; climate adaptation; silvicultural options; dominant trees; risk-ratio meta-analysis